IMPLEMENTATION OF THE PERATURAN BUPATI SIDOARJO NOMOR 72 TAHUN 2017 POLICY CONCERNING PROCEDURES FOR THE PROVISION OF AND RENEWAL OF CERTIFICATES OF APPROPRIATE FUNCTIONALITY (MAP Observer: Jurnal Penelitian Administrasi Publik, 2022)
Indonesia is one of the countries that open cooperation in the industry in the world of course, investors from abroad will work with colleagues in the east java region. Sidoarjo regency is the most business district/company in East Java, businesses that need administrative documents. This researcher knows the implementation of the regulation policy of Sidoarjo Regent on the procedure of granting and renewal of the certificate of building function. The focus of the study was based on four implementation models according to Edward III and implementation variables according to Grindel. To support this study, researchers used 5 people as informants using qualitative data analysis. Based on the results of the study, the implementation of the regulation policy of the regent of Sidoarjo went quite well according to four implementation models and one implementation variable but one implementation model has not worked well, namely communication and information resources so that businesses have not been fully informed about the procedure of granting and renewal of certificates laik building functions.